Real-time monitoring and measurement of wax deposition in pipelines via non-invasive electrical capacitance tomography - Mei, I.L.S. (Institute of Physics Publishing, 2015)
Tomographic analysis of the behavior of waxy crude oil in pipelines is important to permit appropriate corrective actions to be taken to remediate the wax deposit layer before pipelines are entirely plugged. In this study, a non-invasive/non-intrusive electrical capacitance tomography (ECT) system has been applied to provide real-time visualization of the formation of paraffin waxes and to measure the amount of wax fraction from the Malay Basin waxy crude oil sample under the static condition. Analogous expressions to estimate the wax fraction of the waxy crude oil across the temperatures range of 30-50 Â°C was obtained by using Otsu's and Kuo's threshold algorithms. Otsu's method suggested that the wax fraction can be estimated by the correlation coefficient while Kuo's method provides a similar correlation with . These correlations show good agreements with the results which are obtained from the conventional weighting method. This study suggested that Kuo's threshold algorithm is more promising when integrated into the ECT system compared to Otsu's algorithm because the former provides higher accuracy wax fraction measurement results below the wax appearance temperature for waxy crude oil. This study is significant because it serves as a preliminary investigation for the application of ECT in the oil and gas industry for online measurement and detection of wax fraction without causing disturbance to the process flow. Â© 2016 IOP Publishing Ltd.